Konsep Dan Prinsip Keuangan Sosial Islam - Nasution, Edi Marjan; Marliyah, Marliyah; Siregar, Saparuddin (Jurnal Akuntansi dan Pajak, 2024)
Islamic Social Finance has an important role in sharia teachings such as zakat alms and waqf. These principles have long been stated in the Koran and al-Hadith. This research discusses the concepts and principles of Islamic Social Finance contained in the texts and those that apply in Indonesia. The research method "Concepts and Principles of Islamic Social Finance" is (Library research) where relevant library collections are the main strength in this research. This research approach uses normative and sociological methods, namely research based on the Koran and books that discuss public finances in Islam. There are several philanthropic institutions in Indonesia as a forum to help the Muslim community. As an analysis in this research, it was found that philanthropic institutions in Indonesia had different principles and concepts during the previous Islamic period.